THE COMBINATION OF OUTDOOR LEARNING METHOD WITH OBSERVE & REMEMBER GAMES IN TEACHING VOCABULARY AT EIGHT GRADE OF MTS MUHAMMADIYAH AIMAS - Tirta, Riskiah; Nursalim, Nursalim; Nurteteng, Nurteteng (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This study finds out whether or not the combination of Outdoor Learning Method with Observe & Remember Games on English vocabulary of 8th grade students of MTs Muhammadiyah Aimas is successful. This research is a quantitative research with Pre experimental research design. This research was conducted at Mts Muhammadiyah 02 Sorong Regency. The sample of this study was 22 eighth grade students consisting of 12 female and 10 male. The instrument of this research is a test. The test was divided into two tests, namely pre-test and post-test. based on calculations using the SPSS application, it can be obtained that the N-Gain result is 70.54 (70%) which is declared effective. In addition, the result of t-test shows the value of P (0.000) < ? (0.05), which means there is a significant difference between the pretest and posttest. Thus, the alternative hypothesis is accepted (the combination of outdoor learning method with observe & remember game is effective in teaching vocabulary) and the null hypothesis is rejected. In addition, the average score of pretest (41.36) increased to posttest (82.73). In general, the combination of outdoor method with observe & remember game can help students to be more active because students can organize their ideas in learning vocabulary and also remember vocabulary.